The structure of equity risk models - MacQueen, Jason (Henry Stewart Talks, 2007)
Stock risk models for portfolio risk analysis, Generic risk model data, Betas and covariances, Two significant choices about structure and their consequences for estimation error, The impact on portfolio risk forecasts, A short digression on stock selection, Choosing factors
Archived at 2022/04/04